Bioaccumulation of heavy metals in Limnobium laevigatum and Ludwigia peploides: their phytoremediation potential in water contaminated with heavy metals - Fernández San Juan, María Rocío (2018)
Contamination with heavy metals in surface and groundwater is a threat to human health and ecosystems. Due to this, the need arises to remediate water polluted through ecological and profitable technologies, such as phytoremediation. The objective of the work was to evaluate the concentration of lead (Pb) and zinc (Zn) in the floating macrophytes Limnobium laevigatum and Ludwigia peploides, after being exposed to contaminated water experimentally. In this way to be able to determine if these plants have mechanisms that allow them to accumulate the metals in the roots and to perform the translocation of these to different vegetative organs, L. laevigatum and L. peploides were placed in solutions contaminated with Pb ([Pb] = 5 mg/l) and Zn ([Zn] = 20 mg/l). The concentrations of metals in water, root and leaf samples were evaluated as a function of time (0, 1, 2 and 4 days). The determination of the metals was performed by the atomic absorption spectrophotometry technique. After 4 days of exposure to Pb and Zn, the plants showed high metal removal efficiencies of water, more to 70% in all cases. Pb was accumulated fundamentally by roots, while Zn was accumulated more in the leaves. In addition, the bioconcentration and translocation factors for each metal were calculated.